Konsep Keteladanan Terhadap Pendidikan Moral Perspektif Al-Qur’an Dan Hadits Di Era Globalisasi - Rifa, arifatus_10 (IAIN Ambon, 2024)
The term exemplary is considered the most convincing approach to achieving success in forming morals. Weakness in showing examples by educators, especially in implementing Islamic values, is one of the main factors causing a moral crisis. This research aims to evaluate the exemplary method in Moral Education from the perspective of the Al-Qur'an and Hadith. The research method used is library research, where information is collected from various literary sources such as books, journal articles and other sources. The results of this research include: 1. Understanding the exemplary method, 2. Moral education, 3. The concept of exemplary in the Al-Qur'an and Hadith, 4. Al-Qur'an and Hadith Moral education, 5. Exemplary methods in moral education in this era Globalization, 6. Application of Moral Education Values in the concept of Role Modeling in the Era of Globalization